The bidirectional effects of APPswe on the osteogenic differentiation of MSCs in bone homeostasis by regulating Notch signaling - Nan Wang; Xiaoyu Shen; Huakun Huang; Runhan Zhao; Habu Jiwa; Zongxin Li; Pei Li; Jixing Ye; Qiang Zhou (Genes and Diseases)
Amyloid precursor protein (APP), especially Swedish mutant APP (APPswe), is recognized as a significant pathogenic protein in Alzheimer's disease, but limited research has been conducted on the correlation between APPswe and the osteogenic differentiation of mesenchymal stem cells (MSCs). The effects of APPswe and its intracellular and extracellular segments on the osteogenic differentiation of bone morphogenetic protein 2 (BMP2)-induced MSCs were analyzed in this study. Our analysis of an existing database revealed that APP was positively correlated with the osteogenic differentiation of MSCs but negatively correlated with their proliferation and migration. Furthermore, APPswe promoted BMP2-induced osteogenic differentiation of MSCs, while APPswe-C (APPswe without an intracellular segment) had the opposite effect; thus, the intracellular domain of APPswe may be a key factor in promoting the osteogenic differentiation of MSCs. Additionally, both APPswe and APPswe-C inhibited the proliferation and migration of MSCs. Furthermore, the intracellular domain of APPswe inhibited the activity of the Notch pathway by regulating the expression of the Notch intracellular domain to promote the osteogenic differentiation of MSCs. Finally, APPswe-treated primary rat bone marrow MSCs exhibited the most favorable bone repair effect when a GelMA hydrogel loaded with BMP2 was used for in vivo experiments, while APPswe-C had the opposite effect. These findings demonstrate that APPswe promotes the osteogenic differentiation of MSCs by regulating the Notch pathway, but its extracellular segment blocks the self-renewal, proliferation, and migration of MSCs, ultimately leading to a gradual decrease in the storage capacity of MSCs and affecting long-term bone formation.